2014
DOI: 10.3762/bjnano.5.27
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular biosynthesis of gadolinium oxide (Gd2O3) nanoparticles, their biodistribution and bioconjugation with the chemically modified anticancer drug taxol

Abstract: SummaryAs a part of our programme to develop nanobioconjugates for the treatment of cancer, we first synthesized extracellular, protein-capped, highly stable and well-dispersed gadolinium oxide (Gd2O3) nanoparticles by using thermophilic fungus Humicola sp. The biodistribution of the nanoparticles in rats was checked by radiolabelling with Tc-99m. Finally, these nanoparticles were bioconjugated with the chemically modified anticancer drug taxol with the aim of characterizing the role of this bioconjugate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…Both G1 and G2 nanoparticles exhibit the diffraction peaks corresponding to Bragg reflections from (211), (222), (400), (411), (431), (440), (611), (622), (444) and (662) crystal planes, which can be indexed to the cubic structure of Gd 2 O 3 nanoparticles . This is in good agreement with the literature (Abdullah et al 2015;Khan et al 2014). The average crystallite size of G1 and G2 nanoparticles is found to be 30 and 56 nm, respectively.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Both G1 and G2 nanoparticles exhibit the diffraction peaks corresponding to Bragg reflections from (211), (222), (400), (411), (431), (440), (611), (622), (444) and (662) crystal planes, which can be indexed to the cubic structure of Gd 2 O 3 nanoparticles . This is in good agreement with the literature (Abdullah et al 2015;Khan et al 2014). The average crystallite size of G1 and G2 nanoparticles is found to be 30 and 56 nm, respectively.…”
Section: Methodssupporting
confidence: 82%
“…Gd 2 O 3 nanoparticles find applications in bioimaging (when tagged with fluorescent dyes) (Dosev et al 2006), in magnetic resonance imaging as contrast agent (Fortin et al 2007; Khan et al 2014) and in drug delivery (Khan et al 2014). They are also used as neutron convertors in imaging plate neutron detector (Bhattacharyya and Agrawal 1995;Gunduz and Uslu 1996;Khan et al 2014), as additives in UO 2 fuel rods (Gunduz and Uslu 1996;Khan et al 2014), in ZrO 2 to enhance its toughness (Bhattacharyya and Agrawal 1995;Chen 1996;Khan et al 2014), as a radiosensitizer (Duc et al 2011;Miladi et al 2015;Mowat et al 2011;Rancoule et al 2016;Rima et al 2013), as a catalyst (Hussein 1994;Perevalov et al 2014) and dopants for laser (Perevalov et al 2014) and colourants (Perevalov et al 2014) for special glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Figure S2D shows the spectra of N 1s, which contained two components at 398.5 and 399 eV that were attributed to neutral amino groups and amide N atoms. 37,38 The N 1s spectrum was of lower intensity than other spectra, possibly due to near complete reaction of NH 2 groups with CNMA. 39 The existence of a strong Si-O peak at 103 eV indicated that GNP surfaces were coated with silica ( Figure S2E).…”
mentioning
confidence: 99%
“…Typically, Gd 2 O 3 nanoparticles show a very weak broad peak at ca. 325 nm [8] although one would expect some sharp peaks due to many unpaired electrons of Gd. From experience, however, it is known that Gd III compounds has very light pink colour.…”
Section: Resultsmentioning
confidence: 99%